Legitimization tools or governance tools? A systematic literature review of corporate governance and carbon disclosure quality - Zhu, Guifang; Ong, Tze San; Sheikh Hassan, Ahmad Fahmi; Donati, Paolo; Amin, Youssef; Fen, Yap Wing; Liang, Junbo; Pompa, Pier Paolo; He, Sailing (John Wiley and Sons, 2025)
As global climate challenges intensify, corporate carbon disclosure quality (CDQ) has emerged as a vital indicator of corporate environmental transparency and accountability. However, corporate governance (CG) mechanisms remain contested: are they primarily legitimation tools to meet external expectations or governance instruments to ensure substantive environmental performance? This study conducts a systematic literature review (SLR) utilizing the PRISMA framework, methodically screening and synthesizing 64 studies published between 2011 and 2024. Key findings encompass (1) Persistent suboptimal CDQ across both developed and emerging markets; (2) A trend towards theoretical integration, with the CG-CDQ relationship increasingly reflecting the interplay of multiple theoretical frameworks; (3) Dynamic duality of CG's role, wherein its primary function depends on institutional pressure, governance architecture, and stakeholder oversight; (4) Bridging institutional voids in emerging economies, as demonstrated by China's state-owned enterprises (SOEs) surpassing non-state-owned firms under policy incentives. This study also identifies critical research gaps: over two-thirds of CG-CDQ studies concentrate on the US, Europe, and China, while ASEAN and Africa—carbon-intensive regions—remain underexplored, constituting a 90% research void. The cultural dimension is frequently neglected, with only one study examining informal institutions, such as Confucianism. These findings highlight that governments should mandate carbon disclosure standards, implement cross-border accreditation mechanisms, and enhance social oversight; corporations should bolster governance, incorporate environmental expertise, and ensure that 30% of their executives are female; and investors should advocate for ESG performance agreements that correlate carbon disclosure with investment returns, fostering sustainable development.